A linear structural equation modelling of TQM principles and its influence on quality performance. (21st September 2010) - Wong, Choy-Har; Sim, Jia-Jia; Lam, Chee-Hoong; Loke, Siew-Phaik; , Nathan Darmawan
The objective of this study was to examine the structural relationships between TQM practices and quality performance within the Malaysian manufacturing firms. This study was empirically supported by data collected from 116 managers in Malaysia using self-completed questionnaire. Structural equation modelling was applied to analyse the data. The findings revealed that both strategic planning, and information and analysis have strong association with quality performance. This study provides valuable insights for Malaysian manufacturing companies as how to manage their quality performance in order to enhance their capabilities and competencies for long-term sustainability in the marketplaces.